MY SAY: Innovation through a larger network - Abd Razak, Dzulkifli (2009)
The nation's firstever Malaysia High Technology Report will be launched this year. This report will highlight and showcase the many activities of the Malaysian IndustryGovernment Group for High Technology (MIGHT), the compiler of the report. MIGHT was launched as a company limited by guarantee in 1993 and acts as an independent and nonprofit organisation to enable consensus building and coordination of industrygovernment partnership in high technology.